Geostatistical modeling of soil contamination by arsenic and mercury in Mollehuaca, Peru - Tumy-Gomez, Enmanuel Hernan; Arizaca-Avalos, Americo; Huisa-Mamani, Fidel; Apaza-Chino, Julian; Pastor-Contreras, Wilber (Journal of Degraded and Mining Lands Management, 2025)
This study focused on the geostatistical modeling of arsenic (As) and mercury (Hg) contamination levels in soils of the Mollehuaca settlement, Arequipa, Peru, an area significantly affected by artisanal mining. Using advanced geostatistical techniques, such as ordinary kriging, 35 soil samples were evaluated to determine the spatial distribution of these heavy metals and their extreme concentrations. The results showed that As concentrations reached a maximum of 808.00 mg/kg, far exceeding the Environmental Quality Standard (EQS) limit for soils (50 mg/kg) according to D.S. N° 011-2017-MINAM. Similarly, Hg levels presented maximum values of 207.00 mg/kg, also above the threshold of 6.6 mg/kg established by the same regulation. Structural analysis using spherical variograms revealed a high spatial continuity with ranges of 369 m for As and 302.4 m for Hg, indicating that both metals exhibit a strong spatial relationship influenced by geological factors, such as mineralized veins and fractures. This significant correlation between As and Hg, with a determination coefficient r² = 0.6399, suggests a common source of contamination associated with the informal mining practices that characterize this region. In conclusion, the results highlighted the urgent need to implement remediation measures in the most affected areas, as the concentrations of these metals exceed the limits established by Peruvian regulations, representing a considerable risk to human health and local ecosystems. Additionally, continuous monitoring is recommended to improve environmental management and reduce the negative impacts of artisanal mining in this critical area of southern Peru.